Hydrogen-Atom-Assisted Tautomerization on Solid Surfaces-The Case Study of Thioacetamide - Góbi, Sándor; Reva, Igor; Ragupathy, Gopi; FAUSTO, RUI; Tarczay, Gyorgy (American Chemical Society, 2024)
Amorphous thioacetamide (TA) ice was prepared by deposition on a low-temperature substrate in an ultrahigh-vacuum simulation chamber, exposing the sample to a beam of hydrogen atoms. The structural changes were monitored by reflection-absorption FT-IR spectroscopy. The spectral data unambiguously evidence the formation of the higher-energy thiol tautomeric forms of TA upon interaction with H atoms, resulting from the more stable thione tautomer, which is otherwise exclusively present in unprocessed ice. The regeneration of the thione species from the thiol tautomeric forms occurs upon heating the sample above 100 K. Quantum-chemical computations were conducted to confirm the conclusions drawn from the experimental results. According to the theoretical findings, the thiol molecules, formed on the surface of amorphous ice upon H-atom-assisted thione -> thiol tautomerization, cannot survive in the crystalline material. A mechanism for the process at the molecular level is also proposed. This work provides the first example of H-atom-assisted tautomerization occurring on the surface of amorphous ice without the action of UV light as the source of energy.